APAKAH RESIKO PERSEPSIAN MEMODERASI PENGARUH KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN PADA E-COMMERCE? - Elisabet Dita Septiari (Fakultas Bisnis UKDW, 2014)
This study aims to examine the effect customer perceived risks as moderator in the customer satisfaction and customer loyalty relationship. Researcher used convenience sampling survey. The respondents were customers in Yogyakarta that has experienced as online buyer, to be respondent. The hypothesis be tested using hierarchical regression analysis. The findings show that customer satisfaction positively influences customer loyalty. In addition, perceived risks affect the relationship of customer satisfaction and customer loyalty. Keyword: customer satisfaction, customer loyalty, perceived risks